Hemispheric asymmetries in the ionospheric response observed in the American sector during an intense geomagnetic storm - Abreu, A. J. de (2010)
The main purpose of this investigation is to study the ionospheric F region response induced by the intense geomagnetic storm that occurred on 7-8 September 2002. The geomagnetic index Dst reached a minimum of -181 nT at 0100 UT on 8 September. In this study, we used observations from a chain of 12 GPS stations and another chain of 6 digital ionosonde stations. It should be mentioned that, soon after the sudden commencement (SC) at 1637 UT on 7 September, the TEC variations at midlatitude stations in both hemispheres showed an F region positive storm phase. However, during the recovery phase, a strong hemispheric asymmetry was observed in the ionospheric response. While a TID type soliton was observed to propagate in the Southern American sector, no TID activity was seen in the Northern American sector. Also, in the Southern Hemisphere, the TEC variations were less affected by the geomagnetic storm. The Northern Hemisphere observations showed a strong and long-lasting negative F region storm phase starting at about 1000 UT on 8 September (lasting for about 24 h). A perusal of TEC phase fluctuations and equatorial spread-F (ESF) ionospheric sounding data indicates that, on the disturbed night of 7-8 September, some stations showed the occurrence of ESF starting at about 0000 UT (2000 LT) on 8 September, whereas other stations showed that the ESF occurrence started much later, at about 0800 UT (0500 LT). This hemispheric asymmetric response of the ionospheric F region possibly indicates the presence of different mechanisms for the generation of ESF along the various latitudinal regions during the disturbed period.